Cord blood analysis for quicker understanding of health status of community - Dixit, Sujata; Rout, Deeptimayee; Negi, Sapna (International Journal Of Community Medicine And Public Health, 2017)
Background: Cord blood screening of a community could be an easy approach to get an understanding of health status of a community. Hematological and genetic analysis of cord blood is well accepted for gathering information on anemic, congenital defects, infections and genetic disorders in neonate. This information is then used for treatment and preventive therapy. In countries like India, which largely vary in its community setups and its hygiene, the nutritional parameters such studies would be helpful in formulation of customized strategies for upbringing of health in these communities. Methods:In this study we have conducted and compared cord blood haematology screening at rural and urban regions of Odisha which differ specifically in their socio-economic status and genetic but not in other parameters like climatic and environmental status. The rural neonates of Odisha are from low income groups and reside in comparatively unhygienic conditions than urban neonates with middle income background. Results: It was observed that the two populations differ in their lymphocytes and granulocytes counts suggesting differences in infection status of neonates. A difference in mean cell volume and mean cell hemoglobin values were also observed indicates genetic differences in genes related to hematology. Conclusions:Our data shows the effectiveness of cord blood screening of a community to get an assessment of its health status and suggests similar studies on cord blood screening for other parameters like nutritional status of a community. Information so obtained may be used as preventive therapy for stunting, malnourishment etc. to a particular community.